2018
DOI: 10.1002/jsfa.9448
|View full text |Cite
|
Sign up to set email alerts
|

Apoptotic effect of enterodiol, the final metabolite of edible lignans, in colorectal cancer cells

Abstract: BACKGROUND: Enterodiol (END) is transformed by human intestinal bacteria from lignans contained in various whole-grain cereals, nuts, legumes, flaxseed, and vegetables. It is known to have several physiological effects, but its effects on mitogen-activated protein kinase (MAPK) signaling and apoptosis in colorectal cancer (CRC) cells have not yet been elucidated. We therefore investigated the effects of END on apoptosis in CRC cells and whether these effects are mediated via MAPK signaling.RESULTS: Cell prolif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 62 publications
(62 reference statements)
1
14
0
Order By: Relevance
“…Around twelve compounds were identified. The majority compound of free, conjugated, and bound phenolic compounds in both raw and cooked chickpea was enterodiol (46.4–67.42%), a lignan compound with several beneficial properties as an antioxidant and as an inhibitor of some types of cancer [ 54 , 55 , 56 , 57 ]. The rest of the compounds are found in varying amounts and belong to different classes of phenolics ( Table 5 and Figure 5 ): (a) Lignans: Gomisin D (5.81–10.33%) and Anhydro-secoisolariciresinol (12.43–12.78%); (b) Flavonoids: Pelargonidin 3,5- O -diglucoside (1.95–8.67%), Hesperetin 3′,7- O -diglucuronide (5%), 6-Geranylnaringenin (7.46–7.73%), Isorhamnetin (1.55%) and Phloretin 2′- O -glucoside (1.67%); (c) Phenolic acids: p -Coumaroyl glucose (2.90%) and 3,4-Diferuloylquinic acid (6.61%); (d) Other polyphenols: Hydroxytyrosol 4- O -glucoside (3.08–5.62%) and 1,4-Naphtoquinone (3.54%).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Around twelve compounds were identified. The majority compound of free, conjugated, and bound phenolic compounds in both raw and cooked chickpea was enterodiol (46.4–67.42%), a lignan compound with several beneficial properties as an antioxidant and as an inhibitor of some types of cancer [ 54 , 55 , 56 , 57 ]. The rest of the compounds are found in varying amounts and belong to different classes of phenolics ( Table 5 and Figure 5 ): (a) Lignans: Gomisin D (5.81–10.33%) and Anhydro-secoisolariciresinol (12.43–12.78%); (b) Flavonoids: Pelargonidin 3,5- O -diglucoside (1.95–8.67%), Hesperetin 3′,7- O -diglucuronide (5%), 6-Geranylnaringenin (7.46–7.73%), Isorhamnetin (1.55%) and Phloretin 2′- O -glucoside (1.67%); (c) Phenolic acids: p -Coumaroyl glucose (2.90%) and 3,4-Diferuloylquinic acid (6.61%); (d) Other polyphenols: Hydroxytyrosol 4- O -glucoside (3.08–5.62%) and 1,4-Naphtoquinone (3.54%).…”
Section: Resultsmentioning
confidence: 99%
“…Around twelve compounds were identified. The majority compound of free, conjugated, and bound phenolic compounds in both raw and cooked chickpea was enterodiol (46.4-67.42%), a lignan compound with several beneficial properties as an antioxidant and as an inhibitor of some types of cancer [54][55][56][57]. The rest of the compounds are found in varying amounts and belong to different classes of phenolics (Table 5 and On the other hand, there are phenolic compounds in glycosidic form, especially in free phenolic compounds.…”
Section: Identification Of Phenolic Compounds By Uplc-msmentioning
confidence: 99%
“…SDG exhibited positive effects in a variety of model systems, including antioxidant effects in cadmium-induced renal toxicity in rats [ 41 ], anti-inflammatory effects in the dextran sulfate sodium salt-induced colitis mouse model [ 42 ], and cytoprotective and anti-inflammatory effects in human umbilical vein endothelial cells [ 43 ]. SDG and enterodiol have shown apoptotic effects on cultured human colon carcinoma cells [ 44 ] and colorectal cancer cells in vitro [ 45 ], respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The abundance of brown stained nuclei with TUNEL shows apoptosis. Apoptosis increased in SDG treated groups (b2-b4; c2-c4) when compared with control groups (b1; c1) and suppressed the migration of cells in a dose-dependent manner but showed no cytotoxicity (Shin et al, 2019). Despite the fact that using different cancer cell lines, Buckner et al suggested that flaxseed oil can specifically inhibit cancer cell growth and induce apoptosis through caspase-3-dependent pathway in a dose-dependent manner while non-malignant cell lines showed small increases in cell growth (Buckner et al, 2019).…”
Section: Discussionmentioning
confidence: 89%